Two-dimensional frequency modulation jamming to SAR based on ship-borne jammer. Issue 2 (2nd April 2016) - He, Xiaodong; Wang, Zhen; Tang, Bin
Abstract : A two-dimensional frequency modulation deceptive jamming method based on a ship-borne jammer countering for airborne synthetic aperture radar is proposed in this paper. In the beam illuminated area, the jammer intercepts the incident signal transmitted by SAR, modulates an appropriate linear frequency modulation signal rapidly, then amplifies and retransmits the jamming signal to SAR. According to the Range-Doppler algorithm, this paper derives the compression output expression of the Range and Azimuth jamming signal and analyses the relationship between the mismatched signals with the pulse compression network, which are caused by modulated linear frequency modulation parameters and the motion frequency modulation of ship-borne jammer, and the centre displacement, smearing of the pulse compression output both in Range and in Azimuth. Theoretical analysis and simulation results indicate that the modulated mismatched jamming signal could produce a familiar false target beside the jammer, which could confuse the SAR to accurately detect the important target and effectively protect of the moving target. The simulation results verify the feasibility of this jamming method.